Boosting selective nitrogen reduction to ammonia on electron-deficient copper nanoparticles - Yun-Xiao Lin (Nature Portfolio, 2019)
Electrocatalytic nitrogen reduction is promising for ammonia production, but electrocatalysts are limited by low efficiency and high cost. Here, the authors report electron-deficient copper nanoparticles, induced by rectifying contact with polyimide, for selective reduction of nitrogen to ammonia.